Optimization of bioconversion of cassava to sugar for bioethanol production - Noorulnajwa Diyana, Yaacob (Universiti Malaysia Sarawak (UNIMAS), 2011)
Organized by Universiti Malaysia Sarawak(UNIMAS), 3rd - 5th August 2009 at Kuching, Sarawak, Malaysia.